Management concepts of mobile road-builder machinery - Dmitry Yakovlevich Parshin; Denis Gennadyevich Shevchuk (Advanced Engineering Research, 2015)
The work objective is to define the properties of the mobile road-building machinery (MRBM) traffic flows for the control effectiveness improvement. The results of the system analysis of the MRBM control tasks are presented. Their solution concept is presented; the traffic control problem formalization for the mobile road-building machines under the ever-changing conditions of movement is performed. For the first time, system and structural status assessment criteria for MRBM are formulated; the control concepts of the mobile objects groups are analyzed; recommendations for selecting the type of control are given. Mathematical models of the traffic flows establishing the dependence of the motion speed on the traffic density, and a mathematical model of the traffic route optimization for the mobile road-building machinery are presented. Strategies of the adaptive and intelligent control of the mobile objects groups of different numbers, as well as the results of the regression analysis of the mobility objects motion model are presented.